America's Dirty Shame: Living amid Raw Sewage - Flowers, Catherine Coleman (Anglican theological review, 2018)
The article discusses problems with poverty and sewage infrastructure in Lowndes County, Alabama, adapted from a presentation at the February 2017 Trinity Wall Street Conference "Not Just Flint." Topics include the rural and African American population of Lowndes County, public health dangers caused by tropical diseases in poor areas of the U.S., and a study of the county by the organization Alabama Center for Rural Enterprise.